Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Cv Zona Promosindo Di Kota Tangerang Selatan - Ferdinand Alrasyid; Sigit Purnomo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to determine the competence and work discipline on employee performance at CV Zona Promosindo in South Tangerang City. The method used is a quantitative method. This data collection technique is carried out by taking objects from a sample called sampling or respondents, the sampling method uses a saturated sample technique. The research sample is 63 respondents. The data analysis method used in the study includes instrument testing consisting of validity testing, reliability testing, classical assumption testing, and hypothesis testing. From the results of this study it can be concluded that competence has a positive and significant influence on employee performance with a calculated t_value > t_table or or (6.247> 2.000) and a significance value of 0.000 <0.05. Thus, 〖Ho〗_1 is rejected and H_1 is accepted. Work Discipline has a positive and significant influence on employee performance with a calculated t_value > t_table or (4.602> 2.000) and a significance value of 0.000 <0.05. Thus, 〖Ho〗_2 is rejected and H_2 is accepted. Competence and work discipline have a positive and significant influence on employee performance with a calculated F_value > F_table or (27.060> 3.150) and a significance value of 0.000 < 0.05. Thus, 〖Ho〗_3 is rejected and H_3 is accepted. Competence and work discipline on employee performance have a regression effect Y = 13.695 + 0.395 X1 + 0.253 X2 + α. The results of the R-square value (coefficient of determination) of 0.474, it can be concluded that the variables of competence (X1) and work discipline (X2) together have a contribution to the influence of the employee performance variable (Y) of 47.4%, while the remaining 52.6% is influenced by other factors or variables not studied.